2016
DOI: 10.1016/j.jth.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood-based differences in walkability, physical activity, and weight status in India

Abstract: Highlights 1. First to document differences in built environment and physical activity in India. 2. Transport-related physical activity was more predominant among low-SES populations. 3. High-SES populations reported greater leisure-time physical activity. 4. High-SES populations reported longer sitting time and higher BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 85 publications
1
20
0
1
Order By: Relevance
“…Despite these benefits, the mass adoption of private motorized transport and the design of cities to favor automobile use likely resulted in declining levels of active commuting and a rise in population prevalence of overweight, obesity, and related NCDs in India [ 14 ]. Our previous research from India showed that urban living was associated with lower leisure time and transport, physical activity, and increasingly sedentary lifestyles [ 15 , 16 ]. Active commuting may be influenced by characteristics of the neighborhood’s built environments, yet few studies quantify the associations between these factors in India.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these benefits, the mass adoption of private motorized transport and the design of cities to favor automobile use likely resulted in declining levels of active commuting and a rise in population prevalence of overweight, obesity, and related NCDs in India [ 14 ]. Our previous research from India showed that urban living was associated with lower leisure time and transport, physical activity, and increasingly sedentary lifestyles [ 15 , 16 ]. Active commuting may be influenced by characteristics of the neighborhood’s built environments, yet few studies quantify the associations between these factors in India.…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, many observations have been made about PA and slum dwellers. In studying the effect of BE on the PA of citizens of South India, Adlakha et al [51] concluded that people with lower socio-economic status (SES) and living in an area of lower walkability spend more time walking (225 minutes/week) and biking (75 minutes/week) than people with higher SES in an area of high walkability (walking 30 mins/week; biking 1.0 min/week). They attributed the discrepancy to the prohibitive traffic conditions in Chennai, which discourage people with high SES from using their private vehicles.…”
Section: Resultsmentioning
confidence: 99%
“…As one of the first studies conducted on this issue in India, the authors recommended that their findings should be contextualised. In another study, Adlakha et al [51] combined the IPEN with the Neighborhood Environment Walkability Scale (NEWS) to measure the effects of BE on PA. They observed that residents from both lower and higher SES meet the WHO’s recommended levels of PA, yet residents from lower SES get their PA from travel, whilst residents with higher SES obtain theirs from leisure and recreation.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these benefits, mass adoption of private motorised transport and the design of cities to favour automobile use has likely resulted in declining levels of active commuting and a rise in population prevalence of overweight, obesity, and related NCDs in India [14]. Our previous research from India showed that urban living was associated with lower leisure-time and transport physical activity and increasingly sedentary lifestyles [15,16]. Active commuting may be influenced by characteristics of the neighbourhood built environments, yet few studies have quantified the associations between these factors in India.…”
Section: Introductionmentioning
confidence: 99%